Helen Keller. - Davidson, Margaret, 1936-; Watson, Wendy (New York, Scholastic Inc., 1969)
A biography stressing the childhood of the woman who overcame the handicaps of being blind and deaf.
School Library Journal
K-3
Keywords: Keller, Helen, -- 1880-1968 -- Juvenile literature; Keller, Helen, -- 1880-1968.; Blind-deaf -- Biography -- Juvenile literature; Blind; Deaf; Physically handicapped